2021
DOI: 10.1177/21501327211014068
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Service Providers’ Experiences of Accessing Health Services from an Intellectual Disability Health Team

Abstract: A pediatric assessment service for children with Intellectual Disability (ID) was established in a culturally diverse region of Sydney, Australia, to meet the health needs of children and young people with ID. This paper reports on parents’ and providers’ experiences using qualitative and quantitative analysis of surveys. The survey responses from the parents’ enumerated their key concerns and the practical help they received from the service. Responses from service providers reported a high level of satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The three main barriers to the current healthcare and dental services were inadequate healthcare information for PWID, poor communication by the HCW, and difficulty accessing healthcare [ Table 5 ]. This corroborates with previous studies in western countries and a systematic review[ 9 10 , 25 28 ] in Malaysia. However, there was evidence where PWID could not fulfil their need in healthcare,[ 3 ] the evidence of PWID being discriminated against by the doctor or receiving bad attitudes from the staff are still scarce.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The three main barriers to the current healthcare and dental services were inadequate healthcare information for PWID, poor communication by the HCW, and difficulty accessing healthcare [ Table 5 ]. This corroborates with previous studies in western countries and a systematic review[ 9 10 , 25 28 ] in Malaysia. However, there was evidence where PWID could not fulfil their need in healthcare,[ 3 ] the evidence of PWID being discriminated against by the doctor or receiving bad attitudes from the staff are still scarce.…”
Section: Discussionsupporting
confidence: 93%
“…[ 9 ] Other factors such as inadequately trained staff, lack of assessment tools, and poor communication between the family and the service providers also contributed to the parents’ preferences. [ 10 11 ] However, the main reasons for the parents not bringing their children with intellectual disabilities to healthcare facilities were unaware of the existence of services, financial problems, and difficulties in bringing their children because of their behavior. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Parents and carers of PWID had favorable impressions of healthcare services in the current study, which is consistent with a study conducted in Sydney in which the parents spoke well of the clinic. [ 10 ] They had a positive experience overall because they were not stigmatized or subjected to discrimination by the staff, although stigmatizing attitudes toward PWID were also found in previous studies. [ 11 ] Stigma and discrimination can hinder the efforts of healthcare providers to deliver services to individuals with ID and reduce access to treatment.…”
Section: Discussionmentioning
confidence: 60%
“…[ 9 ] In most studies, the authors highlighted the importance of having a positive relationship between parents or caretakers of people with IDs and healthcare professionals as a key factor in positive healthcare experiences and outcomes. [ 4 5 , 10 11 ] The parents or caretakers of children with IDs preferred healthcare workers to communicate directly with their children rather than talk to them during the treatment; however, they claimed that it is hard to find this type of communication in every health institution. [ 12 ] The same study revealed that the lack of communication leads to irritation and tension between parents or caretakers and staff.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring caregivers' experiences of accessing healthcare services for children and young people with complex disabilities indicate that the provision of emotional, social and informational support, or lack thereof, was as important as the medical aspect of care (14) (15) (16) (17). For example, when accessing rehabilitation services, parents of children and young people with cerebral palsy across low-and high-income contexts expressed a desire for information on understanding terms relating to cerebral palsy and how best to support their child's development (18).…”
Section: Introductionmentioning
confidence: 99%